1990
DOI: 10.1093/ajcp/94.2.224
|View full text |Cite
|
Sign up to set email alerts
|

Human Proliferative Sparganosis: A New Japanese Case

Abstract: Human proliferative sparganosis is a rare parasitic disease in which the larval cestodes of unknown species proliferate in the various organs in the whole body. The authors describe a patient with innumerable parasites in the buttock and pelvic bone. The parasites were of globular or egg-like forms, up to 3 mm in diameter. Histologically, the wavy tegument, a few layers of epidermal cells, underdeveloped muscle cells, excretory channels, and calcareous corpuscles were found in the parasites. These morphologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…The patient with pulmonary sparganosis first presented with pulmonary symptoms; a chest X-ray revealed diffuse multiple masses with cavitations, while bronchoscopy with a transbronchial lung biopsy was non-diagnostic. 17 Indeed, there are some reports of pulmonary lesions, described as pulmonary proliferating, [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] due to intrapulmonary migration of sparganum but finding the worm in the lungs is very rare. With respect to intraosseous sparganosis, the Thai case included here is the first ever reported.…”
Section: Discussionmentioning
confidence: 99%
“…The patient with pulmonary sparganosis first presented with pulmonary symptoms; a chest X-ray revealed diffuse multiple masses with cavitations, while bronchoscopy with a transbronchial lung biopsy was non-diagnostic. 17 Indeed, there are some reports of pulmonary lesions, described as pulmonary proliferating, [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] due to intrapulmonary migration of sparganum but finding the worm in the lungs is very rare. With respect to intraosseous sparganosis, the Thai case included here is the first ever reported.…”
Section: Discussionmentioning
confidence: 99%
“…The determination of the exact species is of epidemiological interest, but far more importantly, it allowed the exclusion of the more pathogenic S. proliferum. Serological data from the 1990s suggested a close relationship between S. proliferum and S. erinaceieuropaei, 24 and earlier studies postulated that S. proliferum might be a virus-infected or abnormally differentiated S. erinaceieuropaei. 25,26 However, recent genetic inferences from mitochondrial cox1 genes unambiguously showed that S. proliferum is a distinct species from S. erinaceieuropaei in the same order of the Pseudophyllidea.…”
mentioning
confidence: 91%
“…The former is caused by Spirometra erinaceieuropaei and Spirometra decipiens in China16, Japan17, Korea1819, Taiwan20 and Thailand21 and Spirometra mansonoides in the USA22. The latter is caused by the more pathogenic and disseminating Sparganum proliferum , which is reported as occurring only sporadically in Japan23, Taiwan24 and Thailand25 and very rarely in Paraguay, Venezuela, and the USA2627. Spirometra species require two intermediate hosts for the completion of their life cycle.…”
mentioning
confidence: 99%